Exploring the Lived Experience of Early Hypertension: Insights from Traditional Medicine Perspectives - Aryankhesal, Aidin; Ghods, Roshanak; Shojaii, Asie (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To elicit symptoms, risk factors, and habits existing before or right after blood pressure elevation in newly diagnosed patients with hypertension from the traditional Persian medicine perspective. METHODOLOGY: This was a concurrent nested mixed-method study conducted in 2018. We included newly diagnosed cases of hypertension (BP?140/90 mmHg in two consecutive screenings) in the study. In contrast, those who had a history of hypertension or used anti-hypertension medication were excluded. The participants were surveyed and interviewed to identify their temperament and extract their recent experiences with hypertension. The sampling followed the criterion-based purposive technique, and the sample size was defined based on qualitative data saturation. The recorded interviews were transcribed and coded according to Persian medicine until no new code emerged. RESULTS: Twenty participants were interviewed, and two themes were extracted: (i) primary or predisposing factors, such as warm temperament, change of residence, improper eating habits, abrupt cessation of exercise, psychological factors, and irregular sleep patterns, and (ii) early symptoms that occur at the first sign of rising blood pressure, including digestive complaints and changes in body excretion, psychological manifestations, and unclassifiable general symptoms. CONCLUSION: Physicians are advised to pay attention to these items when taking a history from patients to prevent hypertension and treat it at its early stages.